Synthesis and properties of some pyrazole derivatives of 1,2,4-triazole-3-thiol - A. S. Hotsulia; S. M. Kulish (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2020)
Nitrogen-containing heterocyclic compounds play an important role in the modern pharmaceutical industry. This is due to their significant biological potential. 1,2,4-Triazole and pyrazole are known pharmacophores that are responsible for the formation of a wide range of activities. The construction of the target molecule using 1,2,4-triazole and pyrazole is also interesting in terms of the availability of starting reagents and the simplicity of chemical transformations. The combination of these heterocycles in one molecule allows increasing its opportunities of participation in various biological processes.